Deep semantic segmentation of mangrove combining spatial, temporal and polarization from sentinel-1 time series in the Brazilian territory - Moreno, Gabriel Matheus de Souza (2022)
Dissertação (mestrado) — Universidade de Brasília, Instituto de Ciências Humanas, Departamento de Geografia, Programa de Pós-graduação, 2022.